1990
DOI: 10.1128/jcm.28.6.1477-1478.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MicroScan for identification of Enterococcus species

Abstract: Emerging drug resistance of the enterococci necessitates differentiation from group D streptococci and accurate species identification. MicroScan (Baxter Healthcare Corp., West Sacramento, Calif.) has recently developed a microdilution system for identification and antibiotic susceptibility testing of gram-positive cocci. To evaluate the ability of this system to identify Enterococcus species, 100 isolates identified as enterococci by MicroScan were tested by conventional media and 60 isolates of streptococci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Of the 398 Enterococcus isolates tested, MicroScan panels correctly identified 342 of an error rate of 8.6%, which is similar to that reported by others (1,24). The 56 misidentified species were not included in the present MicroScan data management system.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Of the 398 Enterococcus isolates tested, MicroScan panels correctly identified 342 of an error rate of 8.6%, which is similar to that reported by others (1,24). The 56 misidentified species were not included in the present MicroScan data management system.…”
Section: Discussionsupporting
confidence: 80%
“…One of four E. hirae isolates was distinguished from E. durans isolates by the ability to ferment raffinose on the MicroScan panel. It has previously been shown that 75 to 85% of E. hirae strains ferment both raffinose and sucrose whereas E. durans does not ferment either sugar (24). The addition of sucrose fermentation testing helped distinguish three of four E. hirae isolates from the raffinose-negative E. durans isolates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The preparation and inoculation of the RapID STR and MictoScan panels were earried out as recomtnended by the manufaeturers. Appelbaum et al (1), using the RapID STR kit system, and Tritz et al (37), using the MicroScan Giatn Positive panels, showed excellent reproducibility and correct species identification of 94% of Enteroeoeeus species. Enteroeocci exhibited relatively large (3.0-4.0 tntn in diatneter), shiny, grey-white, non-adherent, catalasenegative, fiat, circular surface colonies with slightly irregular edges and variable hetnolysis on the anaerobically incubated brucella blood agar plates.…”
Section: Microbiai Culturing and Identificationmentioning
confidence: 99%